2000
DOI: 10.1017/s1352465800001053
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Health Promotion Stress Workshops for the General Public: A Controlled Evaluation

Abstract: Large-scale cognitive-behavioural Stress Management workshops were run for members of the general public as part of a city-wide mental health promotion campaign. Four groups were compared: a workshop run over one day (Full-Day), one run over two half-days (Half-Day), a non-specific intervention control group, and a waiting list control group. Results indicate that the participants in the workshop groups improved more than those in either of the control groups, supporting the idea that the psychoeducational app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
50
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 26 publications
7
50
0
Order By: Relevance
“…The 1‐day workshop format has been found to be clinically effective in two randomised controlled trials (RCTs). The first found that stress workshops resulted in significantly decreased anxiety scores at 3‐month follow‐up (Brown et al. , 2000), and the second found that self‐confidence workshops led to significantly lower depression scores (Brown et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1‐day workshop format has been found to be clinically effective in two randomised controlled trials (RCTs). The first found that stress workshops resulted in significantly decreased anxiety scores at 3‐month follow‐up (Brown et al. , 2000), and the second found that self‐confidence workshops led to significantly lower depression scores (Brown et al.…”
Section: Introductionmentioning
confidence: 99%
“…One possible approach to addressing treatment barriers very relevant to EspieÕs (2009) stepped-care model is to deliver CBT-I in a day-long psycho-educational workshop format. This CBT format, aiming to reach large numbers of the general public at once, was originally developed by Brown et al (2000) for stress problems. To maximise accessibility, the workshops were run at the weekend in non-mental health settings, such as leisure centres, and members of the public could directly refer themselves to these workshops rather than relying on GP referral (Brown et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Brown et al . (2000) conclude that given the undoubted unmet need, there are two possible options that could help us to achieve the standards for improving access and choice in primary mental healthcare laid out in the National Service Framework for Mental Health (Department of Health 1999):…”
Section: Introductionmentioning
confidence: 99%
“…There are a few data, particularly economic data, on services and outcomes for youth mental health services in the UK, 10,39 which may be in part because of the rarity of this type of service model. Of the available published evaluations of youth mental health services in the UK, an evaluation of the Youthspace service for [16][17][18][19][20][21][22][23][24][25] year olds in Birmingham 40 found higher levels of engagement, attendance and acceptability. The results for youth advice services for 14-25 year olds 41 showed an improvement in mental health and related stressors, in particular housing, with associated cost savings.…”
Section: Introductionmentioning
confidence: 99%